Organisational and economic characteristics of the baby food products market in Ukraine and EU countries - Aelita Krychkovska; Natalia Zayarnyuk; Ivanna Lobur; Olena Khomenko; Oksana Lopatynska; Iryna Hubytska; Volodymyr Novikov (Pensoft Publishers, 2019)
This article presents the results of the study of problematic issues of organisational-and-economic character concerning the provision of children with baby food products in Ukraine and European Union countries. It is established that the marketing feature of baby food products in Ukraine is its sales from pharmacies. It has been proved that the cost of baby food products in EU countries and in Ukraine have no price gradation depending on the degree of economic development of the country. The dynamics of development of the Ukrainian market of baby food products, as well as the dynamics of the cost of baby food products in Ukraine, depending on their dispensing place, have been analysed. It is established that the cost of baby food products is somewhat lower in pharmacies.